Molecular and serological investigation of hepatitis B virus in patients with acute undifferentiated febrile illness at Tha Song Yang hospital, Tak Province, Thailand - Narin Thippornchai; Anon Sae-Oueng; Akanitt Jittmittraphap; Wang Nguitragool; Pornsawan Leaungwutiwong (BMC Infectious Diseases)
Abstract Background Hepatitis B virus (HBV) infection is associated with hepatitis, often progressing to liver cirrhosis or cancer, posing a significant public health challenge, particularly in Thailand. Previous research revealed that viral causes account for 18.5% of acute undifferentiated febrile illness (AUFI) in Asian countries. This study examined the prevalence of HBV and its seroprevalence among patients with AUFI at Tha Song Yang Hospital (Tak Province, Thailand). Methods A cross-sectional study was conducted using residual serum samples collected between 2016 and 2017 from patients exhibiting symptoms of AUFI at Tha Song Yang Hospital. DNA was extracted and identified for HBV using real-time polymerase chain reaction (PCR). Positive samples were further characterized for the HBV genotype using semi-nested PCR targeting the pre-S gene. The serum samples were subjected to enzyme-linked immunosorbent assay to detect antibodies against hepatitis B core antigen (HBcAg) and hepatitis B surface antigen (HBsAg). Results Among AUFI patients, the prevalence of HBV infection was 6.45% (18 of 279). Genotyping revealed the presence of genotype C with subgenotype C1 (88.89%) and genotype B with subgenotype B3 (11.11%). The seroprevalence of HBcAb and HBsAb was observed in 40.58% (112 of 276) and 48.98% (120 of 245) of the cases, respectively. Conclusions The detection of HBV infection among AUFI patients (6.45%) underscores the spread of HBV within neighboring countries, such as Thailand and Myanmar. Pending confirmation of test results, physicians should maintain vigilance regarding potential HBV infection in AUFI cases. The overall seroprevalence showed 40.58% positivity for HBcAb and 48.98% for HBsAb. Therefore, individuals residing near the Thai border who did not receive the HBV vaccine at birth were recommended to complete a catch-up vaccination series of three doses to mitigate the HBV infection rate and enhance HBV antibody levels.